Weed Management in Pecan - Peter J. Dittmar; Jeffrey G. Williamson (EDIS, 2012)
Weeds compete with pecan trees for light, nutrients, and water. Weed interference can be minimized with proper cultural practices and herbicides. This revised 5-page fact sheet was written by Peter J. Dittmar and Jeffrey G. Williamson, and published by the UF Department of Horticultural Sciences, March 2012.